Pembangunan Ekonomi, Industrialisasi, dan Degradasi Lingkungan Hidup di Indonesia Tahun 1967-2013: Enviromental Kuznet Curve Model - Kurniawan, Andi (Jurnal Ekonomi Kuantitatif Terapan, 2019)
This study aims to identify the impact of economic development and industrialization to  the environmental degradation in Indonesia, both in the long term and short term. To see the effect of economic development and industrialization to the environmental degradation in Indonesia, this research was  used Environmental Kuznets Curve (EKC) model and the model of  Error Correction Mechanism (ECM). The results of the study explain that in the long term, improvement of people's income and industrialization have positive effect linearly with the increase in C02 emissions and at a certain income level there is a process improvement environment characterized by a decrease in CO2 emissions. But in the short term only industrialization which influence on the increase of CO2 emissions Expected that the consensus between the government and businesses (industri) in reducing the impact of pollution and the increased awareness of society in helping to reduce environmental damage.
Keywords: Keywords: economic development, industrialization, degradation, environmental, Enviromnetal Kuznets curve, Error Correction Mechanism